Possible role of gut microbes and host’s immune response in gut–lung homeostasis - Rastogi, Sonakshi; Mohanty, Sneha; Sharma, Sapna; Tripathi, Prabhanshu (Frontiers in Immunology, 2022)
The vast diversity of microbial communities resides on various locations of the human body and they are collectively named as ‘Human Microbiota’. Majority of those microbes are found in the gastrointestinal and respiratory tract. The microorganisms present in the gastrointestinal and the respiratory tract are called as the gut microbiota and the airway microbiota respectively. These microbial communities are known to affect both the metabolic functions and host’s immune responses. Among multiple factors determining the composition of gut microbiota, diet has played pivotal role. The gut microbes possess enzymatic machinery for assimilating dietary fibers and releasing different metabolites, primarily short chain fatty acids (SCFAs). The SCFAs modulate the immune responses of not only the gut but other distal mucosal sites also such as lungs. Dysbiosis in normal gut flora is one of the factors involved in the development of asthma and other respiratory disorders. Of note, several human and murine studies have indicated significant cross-talk between gut microbiota and lung immunity, known as Gut-Lung axis. Here, in this review we summarize the recent state of the field concerning the effect of dietary metabolites, particularly SCFAs on “Gut-Lung axis” as well as discuss its impact on lung health. Moreover, we have highlighted the role of “Gut-Lung axis” on SARS-CoV-2 mediated inflammation. Also, to analyze the global research progress on gut-lung axis and to identify the knowledge gap in this field, we have also utilized bibliographic tools Dimension database and VOS viewer analysis software. Through network mapping and visualization analysis we can predict the present research trend and possibility to explore new directions.